Posthypoxic behavioral impairment and mortality of Drosophila melanogaster are associated with high temperatures, enhanced predeath activity and oxidative stress. - Habib, P.; Jung, J.; Wilms, G.M.; Kokott-Vuong, A.; Habib, S.; Schulz, J.B.; Voigt, A. (Experimental & Molecular Medicine, 2021)
Hypoxia is an underlying pathophysiological condition of a variety of devastating diseases, including acute ischemic stroke (AIS). We are faced with limited therapeutic options for AIS patients, and even after successful restoration of cerebral blood flow, the poststroke mortality is still high. More basic research is needed to explain mortality after reperfusion and to develop adjunct neuroprotective therapies. Drosophila melanogaster (D.m.) is a suitable model to analyze hypoxia; however, little is known about the impacts of hypoxia and especially of the subsequent reperfusion injury on the behavior and survival of D.m. To address this knowledge gap, we subjected two wild-type D.m. strains (Canton-S and Oregon-R) to severe hypoxia (<0.3% O2) under standardized environmental conditions in a well-constructed hypoxia chamber. During posthypoxic reperfusion (21% O2), we assessed fly activity (evoked and spontaneous) and analyzed molecular characteristics (oxidative stress marker abundance, reactive oxygen species (ROS) production, and metabolic activity) at various timepoints during reperfusion. First, we established standard conditions to induce hypoxia in D.m. to guarantee stable and reproducible experiments. Exposure to severe hypoxia under defined conditions impaired the climbing ability and reduced the overall activity of both D.m. strains. Furthermore, a majority of the flies died during the early reperfusion phase (up to 24 h). Interestingly, the flies that died early exhibited elevated activity before death compared to that of the flies that survived the entire reperfusion period. Additionally, we detected increases in ROS and stress marker (Catalase, Superoxide Dismutase and Heat Shock Protein 70) levels as well as reductions in metabolic activity in the reperfusion phase. Finally, we found that changes in environmental conditions impacted the mortality rate. In particular, decreasing the temperature during hypoxia or the reperfusion phase displayed a protective effect. In conclusion, our data suggest that reperfusion-dependent death might be associated with elevated temperatures, predeath activity, and oxidative stress.